Utilization Land Empty Become Toga (Plant Drug Family) In RT 58, Betungan Subdistrict - Eriyanto, Geri Eriyanto; Lestari , Diana Fitri; M, Welly Julita; Al-Rasyid , Muhammad Haikal; Rizkiyansah, Nur Fazril; Afriani, Ririn; Nur’aini, Hesti; Handayani, Tita (Universitas Dehasen Bengkulu, 2025)
Family medicinal plants (TOGA) provide many benefits in human life. Since ancient times, these efficacious plants have been used by people as herbal medicines. From this, the KKN-T work program was carried out to provide knowledge and understanding of the benefits of TOGA. This KKN-T activity was carried out in RT 58, Betungan Village, Selebar District, Bengkulu City Regency. In RT 58, there are still many empty lands of residents. The activity began by asking permission from government officials, RT 58 Management and residents to conduct socialization about TOGA and create a TOGA garden. From the socialization carried out, it can be said that the residents of Bogak Besar Village were quite enthusiastic in listening to the socialization about the use of empty land for TOGA.